A comparative study on high-temperature air oxidation of Cr-coated E110 zirconium alloy deposited by magnetron sputtering and electroplating; Surface and Coatings Technology; Vol. 433 - Sidelev D. V. Dmitry Vladimirovich; Poltronieri C.; Bestetti M. Massimiliano; Krinitsyn M. G. Maksim Germanovich; Grudinin V. A. Vladislav Alekseevich; Kashkarov E. B. Egor Borisovich (2022, 2022)
Title screen